LEAN, WORK AND PSYCHOLOGICAL WELL-BEING (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2025)
Many studies have confirmed the existence of a close relationship between job satisfaction and health. The Siena University Hospital introduced the Lean approach to support personnel development / empowerment and promote a constant improvement in work organization, with the aim of creating value for patients, professionals and the whole organization. The purpose of this study was to examine whether the introduction and the development of this improvement approach in healthcare could contribute to the enhancement of psychological wellbeing and employee satisfaction, with a positive value in preventing related stress work. The Lyne & Barrett Employee Wellbeing Questionnaire (EWQ) was administered to employees involved in selected Lean projects carried out at the Siena University Hospital. The EWe is composed of 59 items and it is structured in three areas: organizational wellbeing, working satisfaction and workload. The analysis of the results showed significant evidence of the impact of improvement activities on the working satisfaction and the workload.